Heteromerization between α2A adrenoceptors and different polymorphic variants of the dopamine D4 receptor determines pharmacological and functional differences: Implications for impulsive-control disorders - Casadó Anguera, Verònica (2021)
Polymorphic alleles of the human dopamine D4 receptor gene (DRD4) have been consistently associated with individual differences in personality traits and neuropsychiatric disorders, particularly between the gene encoding dopamine D4.7 receptor variant and attention deficit hyperactivity disorder (ADHD). The α2A adrenoceptor gene has also been associated with ADHD. In fact, drugs targeting the α2A adrenoceptor (α2AR), such as guanfacine, are commonly used in ADHD treatment. In view of the involvement of dopamine D4 receptor (D4R) and α2AR in ADHD and impulsivity, their concurrent localization in cortical pyramidal neurons and the demonstrated ability of D4R to form functional heteromers with other G protein-coupled receptors, in this study we evaluate whether the α2AR forms functional heteromers with D4R and weather these heteromers show different properties depending on the D4R variant involved. Using cortical brain slices from hD4.7R knock-in and wild-type mice, here, we demonstrate that α2AR and D4R heteromerize and constitute a significant functional population of cortical α2AR and D4R. Moreover, in cortical slices from wild-type mice and in cells transfected with α2AR and D4.4R, we detect a negative crosstalk within the heteromer. This negative crosstalk is lost in cortex from hD4.7R knock-in mice and in cells expressing the D4.7R polymorphic variant. We also show a lack of efficacy of D4R ligands to promote G protein activation and signaling only within the α2AR-D4.7R heteromer. Taken together, our results suggest that α2AR-D4R heteromers play a pivotal role in catecholaminergic signaling in the brain cortex and are likely targets for ADHD pharmacotherapy.